Interactive Peer Instruction Method Applied to Classroom Environments Considering a Learning Engineering Approach to Innovate the Teaching–Learning Process - Jessica Rivadeneira; Esteban Inga (Education Sciences, 2023)
Faced with the problem of a need for more student participation and motivation in the teaching–learning process (TLP) due to the persistence of traditional methods, peer instruction (PI) has emerged as an interactive teaching method. It is based on a dynamic of questions and answers to promote student reflection and discussion. Thus, this article shows the applicability of PI, considering a learning engineering approach to innovating the TLP. For this, the historical-descriptive method is used to conduct a literature review and a bibliometric study, evaluating scientific articles in Web of Science (WoS) and Scopus between 2018 and 2022. In addition, in the second stage, the experimental method is used to apply PI in two educational institutions and evaluate its applicability with Likert scales for teachers and students following a quantitative methodology. Consequently, following the analytical-synthetic method, the results indicate that PI the stages, the most relevant aspects, and the conditions to consider in a classroom environment are highly relevant to enhancing its effects. Thus, such applicability is reflected in its positive results in the TLP, considering the learning engineering, and its representation as a flexible and innovative alternative to traditional methods. This is because PI generated benefits for teachers and students, thus encouraging greater satisfaction, motivation, interest, understanding, and student participation.